On the fringe of commentary : metatextuality in ancient Near Eastern and ancient Mediterranean cultures - Aufrère, Sydney,; Alexander, Philip S.; Bouloux, Cyril Jacques.; Pleše, Zlatko. (Orientalia Lovaniensia Analecta ;, 2014)
This volume contains the papers of the second meeting of the international scholarly network "The Hermeneutic of Judaism, Christianity and Islam," held in Aix-en-Provence (September 25-27, 2008). Drawing on Gerard Genette's theory of the five different types of "transtextuality" (Palimpsestes, Paris 1982) - intertextuality, paratextuality, metatextuality, hypertextuality, and architextuality - , the volume discusses the practices of metatextuality as diverse as commentaries, hypomnemata, pesharim, targumim, Talmud, allegoresis, glosses, scholia, catenae, questions-and-responses (erotapocriseis), prophetic extracts, hypotheses, homilies, integumenta and involucra, Keys to Dreams, translations, and transliterations in the ancient Mediterranean and Near Eastern cultures. Presented with an introduction designed to expand and re-contextualize this issue, the eighteen communications discuss common strategies of metatextuality in Greek and Jewish culture as well as its various manifestations in the Septuagint and other Jewish texts, in the literature of the Ancient Near East and Egypt, in the Greco-Roman world, and in the late antique and medieval literature.